Sorus Characteristics of Ferns (Pteridophyta) in Green Open Spaces at Medan State University - Ritonga, Yusran E.; Hardiansyah, Dadang; Harsono, Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The green open spaces of Medan State University play a role in biodiversity and ecology. Data collection of fern (Pteridophyta) species in the sporophyte phase and characterization of their sori have not been previously reported, so scientific data collection and presentation are needed. The research method used to obtain data is exploratory. Each fern found was documented and collected for herbarium purposes and detailed sorus observation. Twelve fern species from 7 families were identified: Aspleniaceae, Athyriaceae, Davalliaceae, Nephrolepidaceae, Polypodiaceae, Pteridaceae, and Thelypteridaceae. Of the species found, it was noted that they have terrestrial, epiphytic, and terrestrial/epiphytic life forms. Each species has sori located under the leaf surface, except for Davallia denticulata (Burm.f.) Mett. which is at the leaf tip. The position of the sori is parallel to the leaf veins, between the leaf veins, on the leaf margin, and close to the leaf margin. The sori are brown, light brown, reddish brown, gray, and green. This fern has eight sori, each with an annulus. This sori characteristic differentiates and identifies the type of fern. Pteridophytes in the green open spaces of Medan State University play a role as pioneers, builders of biodiversity and ecosystems, and sources of knowledge, food, and medicine. These findings will serve as a source of scientific knowledge and a basis for characterizing sori elsewhere.